2016
DOI: 10.1007/s13187-016-1130-2
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Knowledge About HPV and HPV Vaccine Among Romanian Women

Abstract: Cervical cancer is one of the most prevalent gynecological malignancies worldwide. Romania has the highest incidence of this type of cancer in Europe. A successful prevention strategy has to consider the primary prevention measures (including health education on human papilloma virus (HPV) infection but also vaccination). The aim of this study was to assess the knowledge and attitudes of Romanian women about HPV and HPV vaccine. We conducted a cross-sectional study survey of 454 women using an anonymously comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
2
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 12 publications
4
25
2
1
Order By: Relevance
“…For example, in other Balkan countries, the situation regarding CC and HPV knowledge is generally quite poor. In Romania, even though the majority of interviewed women had heard of HPV, the level of knowledge was low, especially about risk factors for infection [30]. Likewise, Greek adolescents were also insufficiently informed about risk factors and protection methods against CC [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in other Balkan countries, the situation regarding CC and HPV knowledge is generally quite poor. In Romania, even though the majority of interviewed women had heard of HPV, the level of knowledge was low, especially about risk factors for infection [30]. Likewise, Greek adolescents were also insufficiently informed about risk factors and protection methods against CC [31].…”
Section: Discussionmentioning
confidence: 99%
“…Research performed in Slovenia [33] that included women of a wide range of ages and research that included adolescents from Greece [31] also noted low awareness of HPV. On the other hand, studies in the UK [35] and in neighboring Romania [30] showed that between two thirds and three quarters of questioned women had heard about HPV. Such a result was also recorded in our study among subjects that finished medical high school and those attending a medical faculty.…”
Section: Discussionmentioning
confidence: 99%
“…Pain is viewed as a subjective phenomenon or as a perception of an unpleasant emotional or sensual experience associated with a current or potential wound. Pain can only be perceived or experimented by an individual when certain impulses reach the level of the conscious mind interpreted as painful [7][8][9][10].…”
Section: Abstract: Locoregional Anaesthesia Oro-maxillo-facial Terrmentioning
confidence: 99%
“…During last decade the key dental materials used in direct pulp capping are un-doubtfully the bioactive endodontic cements such as MTA or Biodentine, which are increasingly replacing the old-timer calcium hydroxide since they proved to be both efficient suppressors of prostaglandins and pro-inflammatory cytokines, and upregulators of odontoblast-like cells differentiation or growth factors involved in pulp regeneration [37][38][39].…”
Section: Extending the Direct Pulp Capping In Endodontic Pathologymentioning
confidence: 99%
“…Relying on the improvement that bioactive endodontic cements brought in healing ability of pulp injuries, despite the conventional advice of performing the direct pulp capping only in mechanical or traumatic exposure, the vital therapy by this procedure was also successfully extended either in clinical cases of carious exposure having the size of pulp chamber opening up to 2.5 mm or in cases associated with reversible pulpitis, irreversible pulpitis, and even early periapical radiolucency [36,[38][39][40].…”
Section: Extending the Direct Pulp Capping In Endodontic Pathologymentioning
confidence: 99%